2021
DOI: 10.1007/s11325-021-02316-0
|View full text |Cite
|
Sign up to set email alerts
|

Proof of principle study: diagnostic accuracy of a novel algorithm for the estimation of sleep stages and disease severity in patients with sleep-disordered breathing based on actigraphy and respiratory inductance plethysmography

Abstract: Purpose In this proof of principle study, we evaluated the diagnostic accuracy of the novel Nox BodySleepTM 1.0 algorithm (Nox Medical, Iceland) for the estimation of disease severity and sleep stages based on features extracted from actigraphy and respiratory inductance plethysmography (RIP) belts. Validation was performed against in-lab polysomnography (PSG) in patients with sleep-disordered breathing (SDB). Methods Patients received PSG according to AAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…On the other hand, ( 11 ) obtained a κ of 0.65 for wake-NREM-REM classification with pulse photoplethysmography in OSA patients with a median AHI of 16.8. Their performance was superior, but the used CNN was fed with a sequence of 100 epochs of 30 s. Similarly, ( 9 ) reached a κ of 0.62 for wake-NREM-REM using actigraphy and RIP in patients with an average AHI of 19.0. Their algorithm required a manual feature extraction on 25 epochs of 30 s. Although the current network reached lower κ scores compared to the latter studies, it offers a realistic approach for sleep-wake classification with unobtrusive sensors, as it is based on single 30 s epochs.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…On the other hand, ( 11 ) obtained a κ of 0.65 for wake-NREM-REM classification with pulse photoplethysmography in OSA patients with a median AHI of 16.8. Their performance was superior, but the used CNN was fed with a sequence of 100 epochs of 30 s. Similarly, ( 9 ) reached a κ of 0.62 for wake-NREM-REM using actigraphy and RIP in patients with an average AHI of 19.0. Their algorithm required a manual feature extraction on 25 epochs of 30 s. Although the current network reached lower κ scores compared to the latter studies, it offers a realistic approach for sleep-wake classification with unobtrusive sensors, as it is based on single 30 s epochs.…”
Section: Discussionmentioning
confidence: 93%
“…The following studies developed specific sleep staging algorithms for OSA patients based on cardiac and respiratory information. Often, feature-based approaches were implemented to differentiate between sleep stages when expert knowledge was available (7)(8)(9)(10). This implied a disadvantage of the method as prior knowledge was required to find appropriate features.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the classifier to the literature is difficult, on the one hand, as studies generally use a sequence of multiple epochs as input. Korkelainen et al [ 17 ] and Dietz-Terjung et al [ 18 ] developed deep learning networks for Wake-REM-NREM classification in suspected OSA patients, respectively, based on PSG PPG and PSG RIP with actigraphy. Both studies reached a k score larger than 0.60.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent proof of principle study, a sufficient match with polysomnography was found with further developed evaluation algorithms using artificial intelligence based on actigraphy and respiratory excursion data. Thus, with a significantly simplified recording technique, a greatly simplified diagnosis of sleep-related respiratory disorders could be established [31]. Drowsiness is a common symptom of OSA that can resolve with successful treatment.…”
Section: Increasing Recognition Of Actigraphy In the Field Of Sleep Medicinementioning
confidence: 99%